2012
DOI: 10.2147/jir.s33569
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo stimulation of whole blood as a means to determine glucocorticoid sensitivity

Abstract: PurposeGlucocorticoids are commonly prescribed to treat a number of diseases including the majority of inflammatory diseases. Despite considerable interpersonal variability in response to glucocorticoids, an insensitivity rate of about 30%, and the risk of adverse side effects of glucocorticoid therapy, currently no assay is performed to determine sensitivity.Patients and methodsHere we propose a whole blood ex vivo stimulation assay to interrogate known glucocorticoid receptor (GR) up- and downregulated genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Recently, Burnsides et al [839] have developed an ex vivo stimulation assay that determines the ability of leukocytes to upregulate anti-inflammatory genes such as GILZ and FKBP51 following exposure to dexamethasone. It is reasonable that a similar test may be developed to gene profiling lymphoid malignancies prior to and following GC treatment, where upregulation of the pro-apoptotic Bim gene would be a favorable predictor.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Burnsides et al [839] have developed an ex vivo stimulation assay that determines the ability of leukocytes to upregulate anti-inflammatory genes such as GILZ and FKBP51 following exposure to dexamethasone. It is reasonable that a similar test may be developed to gene profiling lymphoid malignancies prior to and following GC treatment, where upregulation of the pro-apoptotic Bim gene would be a favorable predictor.…”
Section: Discussionmentioning
confidence: 99%
“…Basically, Dex is a kind of synthetic glucocorticoid which has an anti-inflammatory and immune-suppressive effects, then it could suppress the response of the immune system by inhibiting the secretion of pro-inflammatory cytokines such as TNFα and IL-6 [6,7]. Based on Galon et al (2002), glucocorticoid does not fully provide suppressive effects, but it could provide stimulant effects for several cells that associated with the immune system i.e.…”
Section: Dexamethasone Increase Population Number Of B Progenitor Celmentioning
confidence: 99%
“…Several methodologies have been investigated for determining cellular GC responsiveness in circulating human blood cells. 5 7 Vermeer et al 6 showed that GC-induced upregulation of the FK506 binding protein 5 ( FKBP5 ) in human leukocytes could be used as a marker of GC responsiveness. FKBP5 interacts with the glucocorticoid receptor (GR) and the subsequent GR-associated transcription machinery.…”
Section: Introductionmentioning
confidence: 99%
“… 8 Burnsides et al found similar upregulation in experiments using FKBP5 and the GC-induced leucine zipper ( GILZ ) gene, which is involved in the regulation of inflammation. 5 However, these assays have only been used in limited studies of altered GC responsiveness in clinical states that involve GC dysregulation 5 , 6 and the assays have not been evaluated in states of severe inflammation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation